Strategies for effective waste management in hydropower construction projects - Hishila Sujakhu; Warangkana Jutidamrongphan (Renewable Energy and Sustainable Development)
Construction materials employed in the sustainable design are commonly subjected to wide network of processing, extracting and transporting steps that are needed in creating the end products. Excess quantity and improper utilisation of the construction materials are the root-cause of the construction waste generation. These wastes probably contribute a major negative impact on the environmental sustainability. With regard to this, the present study investigates the construction waste generation and management practices in hydropower project. In order to work on the objective of the research, the study adapts quantitative research methodology. Data for the present research are collected from 195 experts working in the construction of hydropower project. Purposive sampling is employed in selecting the respondent population for the present research. Collected data are analysed using with statistical tests such as one-way ANOVA, paired sample t test, bivariate and partial correlation analysis and regression analysis in SPSS tool. The overall results of the research disclose that metals such as iron and steel and plastics are observed to have major contribution in waste generation. These construction wastes are observed to have major impact on the environmental sustainability. Economic burdens are reported to be major issues faced during the waste management practices. Also, implementation of 3R strategies are observed to have neutral response from the respondent population. There is a significant relationship between proper and adequate storage of construction materials and waste generation level. In addition to this, corresponding discussion and policy recommendation have been proffered in subsequent sections.   Received: 26 September 2024 Accepted: 06 November 2024 Published: 20 November 2024